Remote Sensing Applications for Sustainable Coastal Habitat Management - R. Uma Devi; Arshid Hussain Malik; K. Bala Chandu (Remote Sensing Applications for Sustainable Coastal Habitat Management, 2022)
The natural habitats such as mangroves, seagrass, salt marshes, coral reefs, coastal lagoons, Estuaries are unique habitats for the coastal biodiversity. They provide a wide range of goods and services, such as food supply, regulation of water-quality processes, storm protection, and carbon storage. However, in recent decades, they have been subject to strong anthropogenic pressure and extreme natural disasters. Therefore, it is essential to protect these coastal habitats. Remote sensing and geographic information systems (GIS) provide a systematic, synoptic framework for expanding scientific knowledge of the Earth as a complex system of geophysical events that frequently result in natural hazards, both directly and through interacting processes. Hence, in the present book, the remote sensing applications that supports for sustainable coastal habitat management are presented.